2007
DOI: 10.1016/j.engfailanal.2006.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behaviour of laser repairing welded joints

Abstract: This paper presents a fatigue study in Nd-YAG laser surface repairing welded joints in specimens of two base materials used in mould production. The tests were carried out in a servo-hydraulic machine in tension, under constant amplitude loading, with two stress ratios R = 0 and R = 0.4. Welded specimens were prepared with U notches and filled with laser welding deposits. The fatigue results are presented in the form of S-N curves obtained in welded and non-welded conditions. Complementary measurements of hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…In a previous work [1,2], the authors observed that welded specimens, tested at R = 0.4, presented a similar fatigue resistance to the correspondent non-welded specimens tested for the same stress ratio and also very close to the curve obtained with welded specimens for R = 0. Residual stresses are probably the main factor affecting this fatigue behaviour.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a previous work [1,2], the authors observed that welded specimens, tested at R = 0.4, presented a similar fatigue resistance to the correspondent non-welded specimens tested for the same stress ratio and also very close to the curve obtained with welded specimens for R = 0. Residual stresses are probably the main factor affecting this fatigue behaviour.…”
Section: Introductionsupporting
confidence: 59%
“…In a previous work [1,2], the authors observed (see Figs. 3 and 4) that welded specimens, tested at R = 0, present a significant lower fatigue resistance than the correspondent non-welded specimens tested for the same stress ratio.…”
Section: Experimental Residual Stressesmentioning
confidence: 80%
“…10 compares the S-N fatigue curves for non-welded specimens and welded specimens in P20 steel at R = 0. Two series of tests performed with repaired specimens are show: one for the new welding parameters optimized as indicated above and using two directions for the welds (0°and 45°); the other was previously obtained [8] using the currently welding parameters used in the mould industry. It can be clearly observed an important increase of the fatigue resistance with the optimized welding procedure previously described.…”
Section: Lp Borrego Et Al / Engineering Failure Analysis XXX (2008mentioning
confidence: 99%
“…A fatigue analysis of the H13 and P20 mould steels with surface defects repaired by the laser process will be performed with several filler materials, welding parameters and welding geometry. The fatigue data obtained with the new welding conditions will be compared with the previously obtained S-N curves in welded and plain specimens [8]. Finally, microhardness analysis and evaluation of the residual stress state of the laser welded regions as well as SEM observations will also be performed after laser repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation